Modes of Expression of Interlingual Transformations in the Translation of The Novel “A Christmas Carol” by Charles Dickens - Sakaeva, Liliya Radikovna; Yahin, Marat Aidarovich; Bazarova, Liliya Vyazirovna (Journal of History Culture and Art Research, 2019)
Translation is considered to be one of the oldest human activities; its role is significant in formation of nation and world cultures. The given research is devoted to the study of interlingual transformations peculiarities based on the fiction work “A Christmas Carol” by Charles Dickens. The relevance of the work is presenting of a modern research and analysis of interlingual transformations in the field of translation. The accumulation of researches on peculiarities of interlingual transformations within the framework of fiction texts translation from English into Russian can help to achieve a high quality of literary translation. The novelty of the given research is in studying a phenomenon on the basis of a new material – the translation of the novel “A Christmas Carol” by Charles Dickens from English into Russian, the analysis of modes of expression of interlingual transformations. The study can contribute to further development of general theory of translation studies and stylistics.